Про написання історії народів і держав - Магочій, П. (Інститут історії України НАН України, 2008)
This paper analyzes approaches on a writing of history of people and the states. The author, on example Poland, Slovakia and Ukraine ascertains, that histories nationalizing states here dominate. It considers such approach become outdated and asserts, that all historical nationalities, connected with territory the certain state should be presented in his grand -narrative.